Cesarean Scar Pregnancy: Always surgical? A Case Report - Cassana, Alessandra (2018)
Cesarean scar pregnancy (CSP) is a rare type of ectopic pregnancy that should be diagnosed early in order to seek the best therapeutic option. We present a case of CSP initially misdiagnosed as a non-viable pregnancy that undergone curettage. Patient was referred to our institution where conservative medical management with methotrexate failed, and the only option was surgical resection of CSP. CSP should be suspected and diagnosed as early as possible. In low-income countries the prevention of massive blood loss along with serious maternal morbidity should be priorized. The use of minimally invasive approach should be planned as a first-line treatment over medical management.